2024
DOI: 10.2339/politeknik.1028437
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Design Criteria for Composite Drive Shaft in Automobiles

Abstract: Thanks to their superior properties such as light weight, higher strength and stiffness, corrosion resistance, the use of plastic matrix composites become attractive in many applications. The weight reduction in the automotive sector is one of these applications. By use of plastic matrix composites, weight and CO2 emission reduction in automobiles could be achieved easily. In this study, carbon fiber and epoxy matrix were processed via filament winding method to produce composite drive shaft. Prior to producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Since weight has a significant impact on automobile performance, it is practical to improve it by replacing traditional heavy drive shafts with composite ones. Weight savings ranging from 24% to 80% have been recorded by researchers [7], [11]- [13] when employing FRP composite driveshafts in place of steel driveshafts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since weight has a significant impact on automobile performance, it is practical to improve it by replacing traditional heavy drive shafts with composite ones. Weight savings ranging from 24% to 80% have been recorded by researchers [7], [11]- [13] when employing FRP composite driveshafts in place of steel driveshafts.…”
Section: Introductionmentioning
confidence: 99%
“…The findings also showed that the torsional characteristics of the composite shafts are significantly influenced by the fiber orientation angle. Modelling and analysis of composite drive shafts for several ply angles and layer counts were performed and so the safest design criterion was determined by Altin et al [7]. The numerical results showed that the 10-layer model with a winding angle of +/-45 degrees has the lowest cost regarding strength.…”
Section: Introductionmentioning
confidence: 99%
“…These components are assembled with snap-fits. Plastic composite materials have become popular recently, thanks to weight reduction efforts in the automotive industry [40]. In order to evaluate the use of wood plastic composite material instead of the components obtained by using ABS in the automotive sector, an I-type snapfits model was analyzed in the ANSYS environment and the results were examined.…”
Section: Introductionmentioning
confidence: 99%